Elaboración De Aditivos Para El Pavimento Asfaltico A Partir Del Plástico, Caucho De Neumático, Y Asfalto Recuperado Como, Una Solución Sostenible En La Pavimentación De Vías. - Córdoba Cubillos, Jeyson Camilo (Universidad Antonio Nariño, 2023)
This project is based on generating new raw materials that provide an improvement to the final product, making the consumer public aware of caring for the environment through the disposition of the material and the publicity of the elaborative process for the final product. In the In practice, the procedure will use solid waste from consumption as raw material domestic, commercial, and industry for road construction, emphasizing the plastic, rubberized materials, and recycled asphalt. The objective is to know the procedure for develop a material that can be added as a substance, which when mixed with the asphalt generate a modified product with improved features